A statistical study on ELF‐whistlers/emissions and M ≥ 5.0 earthquakes in Taiwan. Issue 6 (19th June 2013) - Liu, J. Y.; Wang, K.; Chen, C. H.; Yang, W. H.; Yen, Y. H.; Chen, Y. I.; Hatorri, K.; Su, H. T.; Hsu, R. R.; Chang, C. H.
Abstract : [1] In this paper, we conduct statistical approaches to study the potential relation between ELF‐whistlers/emissions below 100 Hz and 20 M ≥ 5.0 earthquakes occurred in Taiwan in the period from 26 August 2003 to 13 July 2004. Occurrence ratios of the ELF‐whistler and ELF‐emission of the entire study period are computed as the reference backgrounds. Our study shows that the ELF‐whistlers and ELF‐emissions during the earthquake period appear less and more frequently than their associated backgrounds, respectively. For the ELF‐emission, the larger earthquakes generally yield the higher occurrence ratios. The statistical analyses confirm that the occurrence ratios of the ELF‐emission significantly enhance 5–7 days before the earthquakes and are proportional to the earthquake magnitude but inversely to the distance from the observatory to the epicenter. Key Points: The ELF‐emissions significantly enhance before large earthquakes The appearance of the ELF‐emissions is proportional to the earthquake magnitude Less chance observing the ELF‐emissions if far away from the epicenter